Spatial distribution and habitat suitability of seaweed on West Simeulue Island, Aceh Province, Indonesia - Imamshadiqin, Imamshadiqin; Ritonga, Gara Hasonangan; Erlangga, Erlangga; Erniati, Erniati; Imanullah, Imanullah; Syahrial, Syahrial; Salmarika, Salmarika (Universitas Malikussaleh, 2024)
Seaweed is an important biological resource for human life, serving essential ecological functions, including providing shelter and feeding grounds for marine biota. Seaweed can be found in several Indonesian waters, growing naturally or through cultivation, including in the waters around Simeulue Island. This study aimed to assess the distribution of seaweed in relation to land suitability, using oceanographic parameters in Simeulue Island waters. The research was conducted at five stations within the West Teupah District, South Teupah District, and Alafan District. In situ measurements were taken to evaluate land suitability for seaweed growth based on oceanographic parameters such as current speed, depth, substrate type, salinity, temperature, pH, and dissolved oxygen. Results indicated that seaweed in Simeulue Island waters is distributed along the coastline and attached to coral reefs and rocks at depths of 2-5 meters. The total area of seaweed distribution is approximately 351.83 hectares along a coastline of 206.12 km. The measured parameters of seaweed habitats include a pH of 7.7 to 7.9, salinity of 31-35.3 ppt, temperature of 20-30 °C, dissolved oxygen levels of 3-4.8 mg/L, depth of 2-5 meters, current speed of 0.10 to 0.60 m/s, and a sandy coral substrate. Based on these water quality and substrate parameters, the seaweed habitats in Simeulue Island are classified as highly suitable, with suitability values ranging from 64 to 82. The recorded environmental conditions collectively support optimal seaweed growth.